The Influence of Production Flow Rate and Raw Water Turbidity on Distributed Water Turbidity at Lambaro WTP - Fathul Mahdariza (Elkawnie: Journal of Islamic Science and Technology, 2015)
In order to fulfil the high water demand in Banda Aceh City, the Lambaro Water Treatment Plant (WTP) has been operating above its designed capacity. The produced and distributed water quality is decreasing in term of turbidity, as well. It is indicated by some events that the distributed water exceeds the allowed limit. The additional burden is that due to rainy season and human activities at river upstream, the raw water turbidity is higher than expectation in several occasions. This study is conducted to evaluate the influence of production flow rate and raw water turbidity on distributed water turbidity. The data used in this study is acquired from the SCADA system with time range from January to May 2014.